2009
DOI: 10.1111/j.1365-313x.2009.03916.x
|View full text |Cite
|
Sign up to set email alerts
|

The HD‐ZIP IV transcription factor OCL4 is necessary for trichome patterning and anther development in maize

Abstract: ). † These authors contributed equally to this work. SUMMARYAmong the genes controlling the differentiation and maintenance of epidermal cell fate are members of the HD-ZIP IV class family of plant-specific transcription factors, most of which are specifically expressed in the epidermis of tissues. Here, we report the functional analysis of the maize HD-ZIP IV gene OCL4 (outer cell layer 4) via the phenotypic analysis of two insertional mutants, and of OCL4-RNAi transgenic plants. In all three materials, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(168 citation statements)
references
References 46 publications
5
163
0
Order By: Relevance
“…With the notable exception of ZmHDZIV11, which is expressed in mature but not in immature tassels, the expression of most ZmHDZIV genes is more abundant in immature compared with mature organs. This observation is consistent with the functional analysis of ZmHDZIV4_OCL4, which demonstrated that morphological defects in ocl4 mutant leaves and anthers become microscopically detectable at stages when ZmHDZIV4_OCL4 is no longer expressed, but these occur precisely in those tissues that express ZmHDZIV4_OCL4 earlier in development (Vernoud et al, 2009). Extrapolating these observations, ZmHDZIV genes may set the stage in immature organs for developmental events manifesting themselves in mature organs.…”
Section: Widespread Epidermal Expression Among Zmhdziv Genessupporting
confidence: 77%
See 3 more Smart Citations
“…With the notable exception of ZmHDZIV11, which is expressed in mature but not in immature tassels, the expression of most ZmHDZIV genes is more abundant in immature compared with mature organs. This observation is consistent with the functional analysis of ZmHDZIV4_OCL4, which demonstrated that morphological defects in ocl4 mutant leaves and anthers become microscopically detectable at stages when ZmHDZIV4_OCL4 is no longer expressed, but these occur precisely in those tissues that express ZmHDZIV4_OCL4 earlier in development (Vernoud et al, 2009). Extrapolating these observations, ZmHDZIV genes may set the stage in immature organs for developmental events manifesting themselves in mature organs.…”
Section: Widespread Epidermal Expression Among Zmhdziv Genessupporting
confidence: 77%
“…Previous findings in eudicots suggest that this is a general feature of transcription factor genes, which show significantly higher retention than genes fulfilling basic cellular functions (Tang et al, 2008). In addition, one may speculate that the specialization of epidermal functions in land plants necessitated additional control mechanisms, and it may not be a coincidence that all the HD-ZIP IV genes involved in trichome development, which are GL2, HDG11, and HDG12 from Arabidopsis , ZmHDZIV4_OCL4 from maize (Vernoud et al, 2009), and GaHOX1 from cotton (Guan et al, 2008), are members of clade Ib (data not shown for GaHOX1).…”
Section: Conservation Of Two Short Sequence Motifs In the 3# Utr Of Hmentioning
confidence: 99%
See 2 more Smart Citations
“…3A and Dataset S3) (20). OCL4 (OUTER CELL LAYER 4) is an epidermal-specific transcription factor repressing periclinal divisions in the adjacent subepidermal endothecial cells (21), presumably through a mobile signal (22). ocl4 anthers lack all 21-nt premeiotic phasiRNAs despite containing reduced but robust levels of the miR2118 trigger (Fig.…”
Section: Epidermis Is Necessary and Sufficient For Premeiotic Phasirnamentioning
confidence: 99%